Prevalence of postpartum depression and association with risk factors in a tertiary care hospital - Guin, Gita; Rawat, Sarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Postpartum depression also known as postnatal depression is a non-psychotic depressive disorder of variable severity and it can begin as early as after delivery and can persist indefinitely if untreated. The objective of this study was to determine the prevalence of postpartum depression by Edinburgh postnatal depression scale and to evaluate the factors predisposing to postpartum depression. Methods: The present prospective observation study was conducted in the Department of Obstetrics and Gynaecology, Netaji Subhash Chandra Bose Medical College, Jabalpur from 1st March 2015 to 31st August 2016. Participants were screened for postnatal depression using EPDS. A risk factor questionnaire that covered key socio-demographic and obstetrics factors were also completed by all the subjects. Main outcome measure: prevalence of a score of 13 or higher, on the EPDS. The data of the present study was recorded into computer and after proper validation, error checking, coding and decoding, the data was compiled and analysed using the SPSS Window, Appropriate univariate and bivariate analysis were carried out using the fisher exact test or Chi-square test for categorical variables. Results: The present study concludes that the prevalence of postpartum depression is 12.8% (64/500) amongst postnatal women admitted of Obstetrics unit of NSCB Medical College, Jabalpur (Madhya Pradesh) since the prevalence of an EPDS score ≥13 (which is suggestive of PPD) was found in a significant proportion of women, screening for PPD is indicated in all postpartum subjects to identify and promptly treat these women. Identification of a clear association between certain risk factors and PPD will lead to a prompter diagnosis of PPD.